2020
DOI: 10.1371/journal.pone.0236395
|View full text |Cite
|
Sign up to set email alerts
|

The effect of compound kushen injection on cancer cells: Integrated identification of candidate molecular mechanisms

Abstract: Traditional Chinese Medicine (TCM) preparations are often extracts of single or multiple herbs containing hundreds of compounds, and hence it has been difficult to study their mechanisms of action. Compound Kushen Injection (CKI) is a complex mixture of compounds extracted from two medicinal plants and has been used in Chinese hospitals to treat cancer for over twenty years. To demonstrate that a systematic analysis of molecular changes resulting from complex mixtures of bioactives from TCM can identify a core… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Multiple studies have revealed the mechanism of CKI on TNBC. CKI strongly reduces the migration and invasion of MDA-MB-231 cells and induces cell cycle arrest and apoptosis in them (36,37,63,64). Furthermore, CKI has been found to suppress energy metabolism and DNA repair pathways in MDA-MB-231 cells (63).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have revealed the mechanism of CKI on TNBC. CKI strongly reduces the migration and invasion of MDA-MB-231 cells and induces cell cycle arrest and apoptosis in them (36,37,63,64). Furthermore, CKI has been found to suppress energy metabolism and DNA repair pathways in MDA-MB-231 cells (63).…”
Section: Discussionmentioning
confidence: 99%
“…Of particular importance is the use of kushen extracts in combination with extracts from Smilax glabra in compound kushen injection (CKI). CKI has been used in Chinese hospitals to treat cancer for over 20 years ( Cui et al, 2020 ) and has been reported to boost immunity, decrease inflammation, and decrease metastasis ( Wang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…CKI is a TCM formulae extract from kushen ( Radix Sophorae flavescentis ) and baituling ( Rhizoma Heterosmilacis ) at a ratio of 7:3, in which exist hundreds of components including alkaloids and flavonoids ( Cui et al, 2020 ). As approved by the China Food and Drug Administration, CKI can be employed for cancer treatment ( Guo et al, 2015 ) and has several pharmacological functions, including anticancer properties, hemostasis, and immunity enhancement ( Wang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%